A solitary mediastinal mass due to localized AL amyloidosis: case report and review of the literature. (6th March 2013) - Sarosiek, Shayna; Seldin, David C.; Berk, John L.; Sanchorawala, Vaishali
Abstract: AL amyloidosis presenting as a solitary mediastinal mass is a rare occurrence, with only a few cases reported in the literature. We describe a case of a man presenting with a mediastinal mass diagnosed as amyloidosis, confirmed by mass spectrometry to consist of lambda light chains. Here we review the literature and discuss treatment options for this rare entity.